THE IMPACT OF POSTPARTUM FOOD ABSTINENCE ON PERINEAL WOUND HEALING DURATION: A CROSS-SECTIONAL STUDY AT ANUGRAH MULIA CLINIC, INDONESIA - Farlikhatun, Lili; Sari, Dwi Puspita (Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI) Regional Jawa Barat, 2025)
According to the World Health Organization (WHO), approximately 287,000 women died during pregnancy and childbirth in 2020. Sub-Saharan Africa contributed to 70% of these deaths, while South Asia accounted for 16%. In Indonesia, the maternal mortality rate reached 183 per 100,000 live births in 2022. One of the contributing factors to maternal mortality is infection (7.3%). Perineal infections are among the most common postpartum complications. At the Anugrah Mulia Clinic, data from May to June 2023 showed that out of 10 women who delivered vaginally, 90% experienced perineal lacerations, with 40% requiring more than seven days for wound healing, and 10% developing signs of infection. Cultural practices such as food abstinence—avoiding protein-rich foods like chicken, meat, fish, and eggs—may impact nutritional status and delay perineal wound healing. This study aims to examine the effect of food abstinence behavior on the duration of perineal wound healing in postpartum mothers. A cross-sectional analytical design was used, involving a total sample of 36 postpartum women with perineal wounds at the Anugrah Mulia Clinic from November to December 2023, selected through total sampling. The results showed that 44.4% of respondents experienced normal wound healing, while 58.3% did not practice food abstinence. Statistical analysis revealed a significant association between food abstinence and prolonged perineal wound healing (p = 0.003). It is recommended that midwives enhance health education and counseling related to postpartum nutrition to reduce food restrictions and support optimal recovery.